Answer: -15yx^2
Step-by-step explanation:
-12x^2 * y -3x^2 * y=
-12(x^2 * y)-3(x^2 * y)=
(-12-3)(x^2 * y)=
-15x^2 * y=-15yx^2
Answer:
1. C
2. B
3. A
Step-by-step explanation:
You reform the inequality as y, kind of like y= equations. For example x+y ≥ 2 means y ≥ 2 - x.
Anywhere it intersects for both lines it would be shaded red.
X = 36
because angle 108 = 3x
3 x 36 = 108
hope it makes sense, if you have any questions let me know
Step-by-step explanation:
E3, E6, E11, E7: no solution
E1, E12 : 1 solution
E2, E8, E10 : infinite solutions